Childhood adversity accelerates intended reproductive timing in adolescent girls without increasing interest in infants. - Stephanie Clutterbuck; Jean Adams; Daniel Nettle (PLoS ONE)
Women experiencing greater childhood adversity exhibit faster reproductive trajectories. One possible psychological mechanism underlying this phenomenon is an increased interest in infants. Interest in infants is thought to be an adaptation important for successful rearing as it motivates the acquisition of caretaking skills. We investigated the relationships between childhood adversity, intended reproductive timing and interest in infants in a sample of English adolescent girls. Specifically we sought to investigate the relationship between 1) childhood adversity and intended reproductive timing; 2) childhood adversity and interest in infants; and 3) intended reproductive timing and interest in infants. Additionally we explored different methods of measuring interest in infants using self-reported fondness for babies, a forced choice adult versus infant paper-based preference task and a novel computer based attention task using adult and infant stimuli. In total 357 girls aged nine to 14 years participated in the study, which took place in schools. Participants completed the two interest in infants tasks before moving on to a childhood adversity questionnaire. Girls with more childhood adversity reported earlier ideal ages at parenthood. We found some evidence that, contrary to our predictions, girls with less childhood adversity were more interested in infants. There was no relationship between intended reproductive timing and interest in infants. The different measurements for interest in infants were only weakly related, if at all, highlighting the complexity of measuring this construct. Our findings suggest that rather than interest in infants being a mechanism for the effect of childhood adversity on early reproductive timing it might instead be an indicator of future reproductive strategies.